2008
DOI: 10.1182/blood-2008-04-151506
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid precursors are directed to produce dendritic cells as a result of TLR9 ligation during herpes infection

Abstract: Hematopoietic stem and progenitor cells were previously found to express Tolllike receptors (TLRs), suggesting that bacterial/viral products may influence blood cell formation. We now show that common lymphoid progenitors (CLPs) from mice with active HSV-1 infection are biased to dendritic cell (DC) differentiation, and the phenomenon is largely TLR9 dependent. Similarly, CLPs from mice treated with the TLR9 ligand CpG ODN had little ability to generate CD19 ؉ B lineage cells and had augmented competence to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
127
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(135 citation statements)
references
References 51 publications
6
127
1
1
Order By: Relevance
“…Circulating hematopoietic stem cells (HSC) also contribute to the replenishment of the DC pool, and this process is favored by TLR ligands. Indeed, HSC and more differentiated progenitors are directed to differentiate into DC in vitro following LPS stimulation or in vivo following viral infection in mice as a result of TLR9 engagement (17,19). LPS also favors the retention of HSC in tissues and stimulates their local proliferation and their differentiation into DC (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating hematopoietic stem cells (HSC) also contribute to the replenishment of the DC pool, and this process is favored by TLR ligands. Indeed, HSC and more differentiated progenitors are directed to differentiate into DC in vitro following LPS stimulation or in vivo following viral infection in mice as a result of TLR9 engagement (17,19). LPS also favors the retention of HSC in tissues and stimulates their local proliferation and their differentiation into DC (16).…”
Section: Discussionmentioning
confidence: 99%
“…This impairment correlates with a decrease in Ag phagocytosis (14,15). Moreover, in recent years, TLR ligands have been shown to influence hematopoiesis, favoring the retention of hematopoietic progenitors in tissues and stimulating their local proliferation and differentiation into DC (16)(17)(18)(19)(20). This could provide a boost of fresh innate immune effector cells during infections that could sustain the adaptive immune responses against the pathogens.…”
mentioning
confidence: 99%
“…Moreover, they are capable of self/non-self discrimination through Toll-like receptors (TLR), which recognize microbial components. Mouse stem cells and early B-cell progenitors express and use TLR, a mechanism that facilitates their differentiation to the innate immune system (Nagai et al, 2006;Welner et al, 2008b;Welner et al, 2009). Recent work suggests that, as in mice, human primitive cells, including MLP, also express functional TLR (Kim et al, 2005;Sioud & Fløisand, 2007;De Luca et al, 2009;Doulatov et al, 2010).…”
Section: The Early Steps In the Lymphoid Developmentmentioning
confidence: 99%
“…It was recently found that hematopoietic stem cells, as well as multipotent progenitors of human and mouse origin, express TLRs and respond to their ligands by preferentially adopting a myeloid fate (10,11). B lymphocytes also express TLRs and respond to ligand binding by polyclonal activation, proliferation, and differentiation into Ab secretion.…”
mentioning
confidence: 99%
“…Stimulation of common lymphoid progenitors through this receptor inhibits differentiation along the B lineage and stimulates differentiation of dendritic cells (DCs) (11). B cell progenitors express TLR9 (14), but little is known of its role in lymphopoiesis.…”
mentioning
confidence: 99%